Quality of life issues in rural settlements: assessment by social media users - Evgeniy V. Shchekotin; Viacheslav L. Goiko; Darya O. Dunaeva; Polina A. Basina; Julia K. Aleksandrova (Data Science and Management)
Disparity in the quality of life of people living in rural and urban areas is among the major problems, often leading to greater depression among the rural population compared to those in urban areas who have access to a high standard of living. The goal of this study was to identify the issues of the quality of life that are fundamental from the point of view of rural settlements and typical for the rural population in various regions of the Russian Federation with diverse geographical, socioeconomic, and demographic characteristics. The practical relevance of our study is based on the identification of the scope of typical problems related to the quality of life in rural areas. The fundamental value of this study is the significance of digital tracks, which can serve as a source of information. The data sources included messages and posts discussing various quality of life aspects of the rural population published by VKontakte. For this study, we used messages and posts with negative implications from communities in rural settlements in ten Russian regions. These issues include housing infrastructure and utilities, transportation, the environment, telecommunications, banking, healthcare, and education.